Análise espaço-temporal do uso e cobertura do solo do município de Jacundá - SENA, Adriana Passos (2022)
The analysis of the use and occupation of a certain land at different times is considered a way of obtaining knowledge about the changes that have taken place in the space due to the occupation of the same, thus characterizing an anthropic action. Knowledge about these changes, especially in an Amazon region, is of great importance for monitoring the territory, since it is a region that has long been the focus of study in several areas, as well as, for the purpose of monitoring the transformations from space to space. over time identifying the fragility of the environment. In this context, aiming to understand the spatial rearrangements and the dynamics of use and occupation, the present work used images of use and land cover from the platform of MAPBIOMAS BRASIL v 6.0, in the municipality of Jacundá - Pa, in the years of 1985, 1990, 2000, 2010 and 2020, for classification through the Qgis 3.16 software, the classification was made by the color palette, together with vectorization, resulting in the generation of thematic maps classified for the years. The results obtained showed that the use and occupation of the land in the municipality in 1985 were constituted mostly by the forest formation, in contrast in 2020 the pasture class prevails to a greater extent, the municipality in question has been showing forest loss with the increase of anthropic actions , especially with the development of agriculture, resulting in a landscape and economic change in the region.